The Life of Leonardo da Vinci - Castellani, Renato; Instituto Luce. ([S.l.] RAI-Radio Television Italiana, 1972)
Presents the life and works of the Renaissance artist, architect and inventor.
Part I. (1 hr. 15 min.) -- Part II & III (1 hr. 42 min.) -- Part IV & V (1 hr. 42 min.)
English version by Titan Productions, adapted by Peter Solano ; edited by Erno Sethy.
Distributed by Questar Home Video, Chicago, Illinois.
VHS.
Narrator, Guilio Bosetti ; Script and senario, Renato Castellani.
Philippe Leroy as Leonardo.
Keywords: Leonardo -- da Vinci -- 1452-1519.; Artists -- Italy -- Biography; Biography